Composite separator and method of making and use thereof

CN118712651BActive Publication Date: 2026-10-27XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410602214.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2026-10-27
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

隔膜虽不参与电池反应,但隔膜的这些性能指标不仅关系着电池的充放电性能,还影响着电池应用的耐久性和安全性

Benefits of technology

[0018]在本申请的第二个方面,本申请提出了一种制备上述复合隔膜的方法。根据本申请的实施例,该方法包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118712651B_ABST
    Figure CN118712651B_ABST
Patent Text Reader

Abstract

The application discloses a composite diaphragm and a preparation method and application thereof. The composite diaphragm comprises a diaphragm base and a functional layer arranged on at least one side of the diaphragm base. The functional layer comprises inorganic ceramic material, functional additives and a binder. The functional additives comprise at least one of 2,5-di-tert-butyl-1,4-benzoquinone, 2-methylimidazole, 1,3-dimethyl-2-imidazolidinone, trimethyl phosphate and triethyl phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to a composite separator, its preparation method, and its application. Background Technology

[0002] In a battery, the separator serves as the physical barrier separating the cathode and anode. An ideal separator should possess both high ion permeability and electronic insulation to enable rapid ion transfer and maintain efficient energy conversion. Common causes of separator failure include: softening, shrinkage, and even combustion due to high temperatures; short circuits caused by metal dendrites penetrating the separator; and damage from compression or impact. Therefore, practical separators should simultaneously meet requirements such as low thickness, high microporosity, good electrolyte wettability, sufficient mechanical properties, and good chemical and thermal stability. Although the separator does not participate in the battery reaction, these performance indicators not only affect the battery's charge-discharge performance but also its durability and safety in battery applications.

[0003] In related technologies, the main method is to modify the separator by coating it with inorganic ceramic particles to improve its thermal stability. However, this modification method cannot optimize the negative electrode-electrolyte-separator interface, nor can it optimize the path of electrochemical reaction on the positive electrode side during battery discharge. Summary of the Invention

[0004] This application aims to at least partially address one of the technical problems in related technologies. Therefore, the purpose of this application is to propose a composite separator, its preparation method, and its application. This application effectively improves the wettability of the composite separator in the electrolyte by adding highly polar functional additives to the functional layer. Simultaneously, it alters the path of the positive electrode reaction and the morphology of the positive electrode products during discharge, making the positive electrode products more granular rather than extensively distributed. This promotes the uniform and rapid passage of sodium ions through the composite separator to the negative electrode, thereby optimizing the negative electrode-electrolyte-separator interface, thus increasing battery capacity and cycle life.

[0005] In one aspect of this application, a composite separator is provided. According to an embodiment of this application, the composite separator comprises:

[0006] Diaphragm substrate;

[0007] A functional layer is disposed on at least one side of the diaphragm substrate. The functional layer comprises an inorganic ceramic material, functional additives, and a binder. The functional additives include at least one of 2,5-di-tert-butyl-1,4-benzoquinone, 2-methylimidazolium, 1,3-dimethyl-2-imidazolinone, trimethyl phosphate, and triethyl phosphate.

[0008] According to the embodiments of this application, the composite separator effectively improves the wettability of the composite separator in the electrolyte by adding highly polar functional additives to the functional layer. At the same time, it can change the path of the positive electrode reaction and the morphology of the positive electrode products during discharge, making the positive electrode products tend to be granular rather than covered in large areas. This promotes the uniform and rapid passage of sodium ions through the composite separator and their transfer to the negative electrode, thereby optimizing the negative electrode-electrolyte-separator interface, which can improve the battery capacity and cycle life.

[0009] In addition, the composite diaphragm according to the above embodiments of this application may also have the following additional technical features:

[0010] In some embodiments of this application, the mass ratio of the inorganic ceramic material to the functional additive is (5-19):1; or, the mass ratio of the inorganic ceramic material to the functional additive is (13-17):1.

[0011] In some embodiments of this application, the functional additive accounts for 4% to 16% of the mass of the functional layer; or, the functional additive accounts for 5% to 10% of the mass of the functional layer.

[0012] In some embodiments of this application, the inorganic ceramic material accounts for 75.5% to 94.3% of the mass of the functional layer, or 80% to 94.3% of the mass of the inorganic ceramic material in the functional layer; and / or, the adhesive accounts for 0.5% to 5.0% of the mass of the functional layer.

[0013] In some embodiments of this application, the inorganic ceramic material includes at least one of alumina, boehmite, magnesium hydroxide, silicon dioxide, titanium dioxide, and zirconium oxide; and / or, the binder includes at least one of polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylic acid, polyacrylonitrile, and styrene-butadiene rubber; and / or, the membrane matrix includes at least one of polyethylene and polypropylene.

[0014] In some embodiments of this application, the functional layer further includes a dispersant and a wetting agent.

[0015] In some embodiments of this application, the dispersant accounts for 0.1% to 1.0% of the mass percentage in the functional layer; and / or, the wetting agent accounts for 0.1% to 1.0% of the mass percentage in the functional layer.

[0016] In some embodiments of this application, the dispersant includes at least one of sodium carboxymethyl cellulose, polyvinylpyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; and / or, the wetting agent includes at least one of anionic surfactant, polyethylene surfactant, and polyol surfactant.

[0017] In some embodiments of this application, the composite membrane has a thermal shrinkage rate of less than 5% in the MD direction after being baked at 150°C for 1 hour; and / or, the sodium ion transference number of the composite membrane immersed in the electrolyte is 0.2 to 0.6.

[0018] In a second aspect, this application provides a method for preparing the aforementioned composite diaphragm. According to an embodiment of this application, the method includes:

[0019] Inorganic ceramic materials, functional additives, binders, dispersants, wetting agents, and solvents are mixed to form a slurry;

[0020] The mixed slurry is coated on at least one side of the membrane substrate and dried to obtain a composite membrane.

[0021] The method for preparing the composite separator according to the embodiments of this application is simple, easy to implement, and readily industrialized. Furthermore, by adding highly polar functional additives to the mixed slurry, this method effectively improves the wettability of the composite separator in the electrolyte. It also alters the path of the positive electrode reaction and the morphology of the positive electrode products during discharge, making the positive electrode products more granular rather than extensively distributed. This promotes the uniform and rapid passage of sodium ions through the composite separator to the negative electrode, thereby optimizing the negative electrode-electrolyte-separator interface, ultimately increasing battery capacity and cycle life.

[0022] In addition, the method for preparing the composite membrane according to the above embodiments of this application may also have the following additional technical features:

[0023] In some embodiments of this application, the solid content of the mixed slurry is 20wt% to 50wt%.

[0024] In a third aspect, this application proposes a battery. According to embodiments of this application, the battery includes the composite separator described above or a composite separator prepared by the methods described above. This effectively improves the battery's cycle life and capacity.

[0025] In a fourth aspect, this application proposes an electrical device. According to an embodiment of this application, the electrical device includes the battery described in the above embodiments. Thus, the electrical device possesses all the advantages of a battery, which will not be elaborated further here.

[0026] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0027] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0028] Figure 1 This is a schematic diagram of the structure of the composite diaphragm in some embodiments of this application;

[0029] Figure 2 This is a flowchart illustrating a method for preparing a composite diaphragm according to some embodiments of this application.

[0030] Figure label:

[0031] 10-Composite diaphragm, 11-Diaphragm matrix, 12-Functional layer. Detailed Implementation

[0032] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0033] This application was filed by the inventor based on the following questions:

[0034] In related technologies, the main method is to modify the separator by coating it with inorganic ceramic particles to improve its thermal stability. However, while this modification method improves the thermal stability of the separator, it cannot simultaneously optimize the negative electrode-electrolyte-separator interface, nor can it optimize the path of the electrochemical reaction on the positive electrode side during battery discharge.

[0035] In view of this, in one aspect of this application, a composite diaphragm 10 is proposed. According to an embodiment of this application, refer to the appendix... Figure 1The composite separator 10 includes: a separator substrate 11; and a functional layer 12 disposed on at least one side of the separator substrate 11. The functional layer 12 includes an inorganic ceramic material, functional additives, and a binder. The functional additives include at least one of 2,5-di-tert-butyl-1,4-benzoquinone (DBBQ), 2-methylimidazolium, 1,3-dimethyl-2-imidazolinone, trimethyl phosphate, and triethyl phosphate. Therefore, by adding highly polar functional additives to the functional layer 12, this application effectively improves the wettability of the composite separator 10 in the electrolyte. Simultaneously, it alters the pathway of the positive electrode reaction and the morphology of the positive electrode products during discharge, making the positive electrode products more granular rather than extensively distributed. This promotes the uniform and rapid passage of sodium ions through the composite separator 10 and their transfer to the negative electrode, thereby optimizing the negative electrode-electrolyte-separator interface, thus increasing the battery capacity and cycle life.

[0036] The principle by which the composite diaphragm proposed in this application achieves the above-mentioned beneficial effects will be explained in detail below:

[0037] This application improves the thermal stability of the composite separator by adding inorganic ceramic materials to the functional layer. Simultaneously, this application adds highly polar functional additives to the functional layer, including at least one of 2,5-di-tert-butyl-1,4-benzoquinone (DBBQ), 2-methylimidazolium, 1,3-dimethyl-2-imidazolinone, trimethyl phosphate, and triethyl phosphate. This enhances the wettability of the composite separator in the electrolyte, altering the pathway of the positive electrode reaction and the morphology of the positive electrode products during discharge. The positive electrode products tend to be particulate rather than large-scale, promoting the uniform and rapid passage of sodium ions through the separator and their transfer to the negative electrode. This optimizes the negative electrode-electrolyte-separator interface, thereby increasing battery capacity and cycle life. The binder in the functional layer improves its adhesion, ensuring the functional layer is stably positioned on the surface of the separator substrate and preventing it from detaching.

[0038] Specifically, the composite diaphragm of this application has a thermal shrinkage rate of less than 5% in the MD direction after baking at 150°C for 1 hour; at the same time, the sodium ion transference number of the composite diaphragm immersed in the electrolyte is 0.2 to 0.6.

[0039] The MD direction is the longitudinal direction of the composite membrane, and also the coating direction.

[0040] According to some specific embodiments of this application, the mass ratio of inorganic ceramic material to functional additive is (5-19):1, for example, it can be 5:1, 7:1, 9:1, 13:1, 14:1, 15:1, 16:1, 17:1, 19:1, etc. By limiting the mass ratio of inorganic ceramic material to functional additive within the above range, it is possible to improve the thermal stability of the composite membrane while further ensuring enhanced wettability of the composite membrane in the electrolyte, changing the path of the positive electrode reaction and the morphology of the positive electrode products during discharge, promoting the uniform and rapid passage of sodium ions through the composite membrane and their transfer to the negative electrode, thereby optimizing the negative electrode-electrolyte-membrane interface. Preferably, the mass ratio of inorganic ceramic material to functional additive is (13-17):1.

[0041] According to further specific embodiments of this application, the mass percentage of the functional additive in the functional layer is 4% to 16%, for example, it can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12.5%, 15%, 16%, etc. By limiting the mass percentage of the functional additive in the functional layer to the above range, the wettability of the composite membrane in the electrolyte can be further enhanced, the path of the positive electrode reaction and the morphology of the positive electrode products during discharge can be changed, and sodium ions can be further promoted to pass through the composite membrane uniformly and rapidly to the negative electrode, thereby optimizing the negative electrode-electrolyte-membrane interface. Preferably, the mass percentage of the functional additive in the functional layer is 5% to 10%.

[0042] According to some specific embodiments of this application, the inorganic ceramic material accounts for 75.5% to 94.3% of the mass of the functional layer, for example, 75.5%, 80%, 85%, 87.5%, 90%, 92%, 94.3%, etc. By limiting the mass percentage of the inorganic ceramic material in the functional layer to the above range, the thermal stability of the composite separator can be further improved. Preferably, the inorganic ceramic material accounts for 80% to 94.3% of the mass of the functional layer.

[0043] According to some specific embodiments of this application, the mass percentage of the adhesive in the functional layer is 0.5% to 5.0%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5.0%, etc. By limiting the mass percentage of the adhesive in the functional layer to the above range, it is possible to further ensure that the bonding performance of the functional layer is within a reasonable range, so that the functional layer can be stably disposed on the surface of the diaphragm substrate.

[0044] In the embodiments of this application, the specific types of inorganic ceramic materials are not particularly limited, and those skilled in the art can select them according to actual needs. As some preferred options, the inorganic ceramic materials include at least one of alumina, boehmite, magnesium hydroxide, silicon dioxide, titanium dioxide, and zirconium oxide. The above-mentioned types of inorganic ceramic materials can further improve the thermal stability of the composite membrane. Alumina is more preferred.

[0045] In the embodiments of this application, the specific type of adhesive is not particularly limited. Those skilled in the art can select according to actual needs. As some preferred options, the adhesive includes at least one of polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylic acid, polyacrylonitrile and styrene-butadiene rubber. The above-mentioned types of adhesives can effectively ensure the bonding performance of the functional layer, so that the functional layer can be stably set on the surface of the diaphragm substrate.

[0046] In the embodiments of this application, the specific type of the diaphragm substrate is not particularly limited. Those skilled in the art can choose according to actual needs. As some preferred options, the diaphragm substrate includes at least one of polyethylene and polypropylene.

[0047] According to some specific embodiments of this application, the functional layer further includes a dispersant and a wetting agent. In the process of forming the functional layer, functional additives, inorganic ceramic materials, binders, dispersants, wetting agents, and solvents are first mixed to form a slurry. The role of the dispersant is to improve the dispersibility of each material, making the raw materials more uniformly mixed. The role of the wetting agent is to improve the contact between the raw materials and the solvent, thereby improving the wettability of the membrane.

[0048] According to some specific embodiments of this application, the mass percentage of the dispersant in the functional layer is 0.1% to 1.0%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. By limiting the mass percentage of the dispersant in the functional layer to the above range, the dispersibility of each material can be further improved, and the raw materials can be mixed more uniformly.

[0049] According to some specific embodiments of this application, the mass percentage of the wetting agent in the functional layer is 0.1% to 1.0%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. By limiting the mass percentage of the wetting agent in the functional layer to the above range, the contact between each raw material and the solvent can be further improved, thereby improving the wettability of the membrane.

[0050] In the embodiments of this application, the specific type of dispersant is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred options, the dispersant includes at least one of sodium carboxymethyl cellulose, polyvinylpyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0051] In the embodiments of this application, the specific type of wetting agent is not particularly limited. Those skilled in the art can select it according to actual needs. As some preferred options, the wetting agent includes at least one of anionic surfactants, polyethylene surfactants, and polyol surfactants.

[0052] In a second aspect, this application provides a method for preparing the aforementioned composite diaphragm. According to embodiments of this application, refer to the appendix... Figure 2 The method includes:

[0053] S100: Inorganic ceramic materials, functional additives, binders, dispersants, wetting agents and solvents are mixed to form a mixed slurry;

[0054] In this step, inorganic ceramic materials and functional additives are first mixed in a certain proportion, then appropriate amounts of binder, dispersant, wetting agent, and solvent are added. The mixture is then thoroughly stirred and ultrasonicated to ensure uniform dispersion, forming a slurry. The dispersant's role is to improve the dispersibility of each material, making the raw materials more uniformly mixed. The wetting agent's role is to improve the contact between the raw materials and the solvent, thereby improving the wettability of the diaphragm.

[0055] According to some specific embodiments of this application, the solid content of the mixed slurry is 20wt% to 50wt%, for example, it can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc.

[0056] In the embodiments of this application, the specific types of solvents are not particularly limited, and those skilled in the art can choose according to actual needs. As some preferred options, the solvents include at least one of water, N-methylpyrrolidone (NMP), ethanol and acetone.

[0057] S200: The mixed slurry is coated on at least one side of the diaphragm substrate and dried to obtain a composite diaphragm.

[0058] In this step, the mixed slurry from step S100 can be roller-coated onto the diaphragm substrate and vacuum-dried at a certain temperature to obtain a composite diaphragm.

[0059] The method for preparing the composite separator according to the embodiments of this application is simple, easy to implement, and readily industrialized. Furthermore, by adding highly polar functional additives to the mixed slurry, including at least one of 2,5-di-tert-butyl-1,4-benzoquinone (DBBQ), 2-methylimidazolium, 1,3-dimethyl-2-imidazolinone, trimethyl phosphate, and triethyl phosphate, this method effectively improves the wettability of the composite separator in the electrolyte. Simultaneously, it alters the pathway of the positive electrode reaction and the morphology of the positive electrode products during discharge, making the positive electrode products more granular rather than extensively distributed. This promotes the uniform and rapid passage of sodium ions through the composite separator to the negative electrode, thereby optimizing the negative electrode-electrolyte-separator interface, ultimately increasing battery capacity and cycle life.

[0060] In a third aspect, this application proposes a battery. According to embodiments of this application, the battery includes the composite separator described above or a composite separator prepared by the methods described above. This effectively improves the battery's cycle life and capacity.

[0061] In the embodiments of this application, the battery described above can be a sodium metal battery, which includes the composite separator of the above embodiments or the composite separator prepared by the method of the above embodiments. This effectively improves the cycle life and capacity of the sodium metal battery.

[0062] In the embodiments of this application, the battery described above can also be a sodium-ion battery, which includes the composite separator of the above embodiments or the composite separator prepared by the method of the above embodiments. This effectively improves the cycle life and capacity of the sodium-ion battery.

[0063] The following uses a sodium-ion battery as an example to illustrate this. A sodium-ion battery includes a positive electrode, a composite separator, a negative electrode, and an electrolyte. The composite separator is placed between the positive electrode and the negative electrode.

[0064] The positive electrode sheet includes a positive current collector and a positive electrode material layer formed on the positive current collector. The positive electrode material layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.

[0065] For sodium-ion batteries, the positive electrode active material can be one or more of the following, including but not limited to transition metal oxides, polyanionic compounds, organic polymers, and Prussian blue-based materials. In sodium transition metal oxides, the transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; for example, Na is a sodium transition metal oxide. x MO2, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, 0 < x ≤ 1, for example Na[Ni 1 / 3 Fe 1 / 3Mn 1 / 3 O2.

[0066] The aforementioned polyanionic compounds possess sodium ion, transition metal ion, and tetrahedral (YO4) structures. n- A class of compounds with an anionic unit, wherein the transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si; n represents (YO4). n- The valence state, for example, Na3V2(PO4)3.

[0067] The aforementioned Prussian blue compounds are a class of compounds containing sodium ions, transition metal ions, and cyanide ions (CN-), and their general chemical formula can be represented as Na. x M1[M2(CN)6], where 0 < x ≤ 2, and M1 and M2 are at least one of Ni, Cu, Fe, Mn, Co and Zn, respectively.

[0068] The specific materials of the above-mentioned positive electrode binder are not particularly limited. As some specific examples, the positive electrode binder may include, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), and polyacrylic acid (PAA).

[0069] The specific materials of the aforementioned positive electrode conductive agent are not particularly limited. As some specific examples, the positive electrode conductive agent may include, but is not limited to, one or more of acetylene black, conductive carbon black, carbon nanotubes, carbon fibers, graphene, etc.

[0070] In the embodiments of this application, the specific material of the positive current collector is not particularly limited. As some specific examples, the positive current collector may include, but is not limited to, at least one of aluminum foil, carbon-coated aluminum foil, and stainless steel foil.

[0071] In the embodiments of this application, the electrolyte includes an electrolyte salt and an organic solvent. The specific types and compositions of the electrolyte salt and the organic solvent are conventional choices in the battery field and can be selected according to actual needs.

[0072] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of: sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium bis(trifluoromethanesulfonyl)imide (NaN(CF3SO2)2), sodium bis(fluorosulfonyl)imide (NaN(SO2F)2), sodium bis(oxalateborate)borate (NaB(C2O4)2), and sodium difluorooxalateborate (NaBF2C2O4).

[0073] In some embodiments, the organic solvent may include, but is not limited to, at least one of: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), diethylene glycol dimethyl ether (DEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), and tetraethylene glycol dimethyl ether (TEGDME).

[0074] The battery of this application may be in the form of a battery cell, a battery module, or a battery pack. In some embodiments, battery cells may be assembled into a battery module, and the number of battery cells contained in a battery module may be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery module. In some embodiments, battery modules may also be assembled into a battery pack, and the number of battery modules contained in a battery pack may be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery pack.

[0075] In a fourth aspect, this application proposes an electrical device. According to an embodiment of this application, the electrical device includes the battery described in the above embodiments. Thus, the electrical device possesses all the advantages of a battery, which will not be elaborated further here.

[0076] Specifically, the aforementioned electrical equipment can include, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.

[0077] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.

[0078] Example 1

[0079] 1) Preparation of diaphragm

[0080] A PE membrane substrate with a thickness of 9 μm was selected. A mixed dispersion was prepared by mixing and stirring the solvent NMP, binder polyvinylidene fluoride (PVDF), dispersant sodium dodecylbenzenesulfonate (DOS), wetting agent polyvinyl alcohol (PVA), Al₂O₃, and 2,5-di-tert-butyl-1,4-benzoquinone (DBBQ). The solid content of the mixed dispersion was 45 wt%, based on a total mass of 100% for the binder PVDF, dispersant sodium dodecylbenzenesulfonate, wetting agent PVA, Al₂O₃, and DBBQ, a PVDF mass fraction of 3%, a DOS mass fraction of 0.5%, a PVA mass fraction of 0.5%, and a Al₂O₃ to DBBQ mass ratio of 5:1. The mixed dispersion was coated onto the PE membrane and vacuum dried to form a composite membrane.

[0081] 2) Preparation of positive electrode sheet

[0082] The active material (sodium iron pyrophosphate), conductive agent (SP), and binder (PVDF) are mixed evenly in a stirring device at a mass ratio of 95:3:2. Then, a certain amount of solvent (N-methylpyrrolidone) is added and stirred to form a uniform slurry with a solid content of 40 wt%. The slurry is coated onto the positive current collector aluminum foil using a coating machine, dried, and cold-pressed to obtain the positive electrode sheet.

[0083] 3) Preparation of negative electrode sheet

[0084] A 1mm thick sheet of metallic sodium.

[0085] 4) Preparation of electrolyte

[0086] Dry sodium salt NaPF6 was added to a mixed solvent of EC and DMC to prepare an electrolyte with a concentration of 1 mol / L. The volume ratio of EC to DMC was 1:1.

[0087] 5) Assemble the button battery

[0088] The positive electrode, negative electrode, and composite separator are cut into small circular pieces of different diameters using a circular hole slicing machine. In an argon-protected glove box, the positive electrode, separator, and negative electrode are placed in the button cell casing in sequence, with the separator positioned between the positive and negative electrodes. The electrolyte is then added to assemble the button cell.

[0089] Example 2-23

[0090] The preparation methods of Examples 2-23 are basically the same as those of Example 1, with the differences shown in Table 1.

[0091] Example 24

[0092] The preparation method of Example 24 is basically the same as that of Example 5, except that:

[0093] In Example 5, 2,5-di-tert-butyl-1,4-benzoquinone DBBQ was replaced with trimethyl phosphate.

[0094] Example 25

[0095] The preparation method of Example 25 is basically the same as that of Example 5, except that:

[0096] In Example 5, 2,5-di-tert-butyl-1,4-benzoquinone DBBQ was replaced with triethyl phosphate.

[0097] Example 26

[0098] The preparation method of Example 26 is basically the same as that of Example 5, except that:

[0099] In Example 5, 2,5-di-tert-butyl-1,4-benzoquinone DBBQ was replaced with 1,3-dimethyl-2-imidazolinone.

[0100] Example 27

[0101] The preparation method of Example 27 is basically the same as that of Example 5, except that:

[0102] Replace 2,5-di-tert-butyl-1,4-benzoquinone DBBQ in Example 5 with 2-methylimidazole.

[0103] Comparative Example 1

[0104] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that DBBQ is not added, as shown in Table 1.

[0105] Comparative Example 2

[0106] Comparative Example 2 uses PE with a thickness of 9 μm as the separator, and no functional layer is coated on the surface of the PE separator, as shown in Table 1.

[0107] Table 1

[0108]

[0109]

[0110]

[0111] The contact angles between the composite membranes prepared in Examples 1-27 and Comparative Examples 1-2 and the electrolyte were tested, and the results are shown in Table 2. The thermal shrinkage rates of the composite membranes prepared in Examples 1-27 and Comparative Examples 1-2 were also tested, and the results are shown in Table 2.

[0112] The ion transfer number, charge transfer impedance, discharge capacity, and capacity retention after 200 cycles of the batteries prepared in Examples 1-27 and Comparative Examples 1-2 were tested respectively, and the results are shown in Table 2.

[0113] Contact angle test method between composite diaphragm and electrolyte:

[0114] 5 μl of the above electrolyte was dropped onto the composite membrane, and the contact angle between the composite membrane and the electrolyte was tested using a Dataphysics OCA020 contact angle tester.

[0115] Test method for the heat shrinkage rate of composite diaphragms:

[0116] The composite separator to be tested was baked at 150℃ for 1 hour. The dimensional changes of the composite separator in the MD direction (i.e., longitudinal direction) before and after high-temperature baking were recorded. The formula for calculating the thermal shrinkage rate of the composite separator in the MD direction is as follows:

[0117]

[0118] In the formula L a and L b These represent the lengths of the composite diaphragm in the MD direction before and after high-temperature baking.

[0119] Methods for testing the transport number of sodium ions:

[0120] Sodium ion transport number can be measured using a combination of chronoamperometry and electrochemical impedance spectroscopy. The specific steps involve sandwiching a composite separator soaked in electrolyte between two lithium electrodes to assemble a C2032 coin cell for testing. The specific calculation formula is as follows:

[0121] τ Na +=I SS (ΔV-I0R0) / I0(ΔV-I SS R SS )

[0122] Where, τ Na+ The sodium ion transport numbers, I0 and I, refer to the sodium ion transport numbers of the composite membrane immersed in the electrolyte. SS These are the current values ​​obtained by chronoamperometry under the initial and steady-state conditions, respectively, R0 and R... SS It is the resistance value obtained by electrochemical impedance spectroscopy under the initial and steady states, and AV is the voltage value applied during the test (10mV).

[0123] Test method for charge transfer impedance of battery:

[0124] The assembled battery was subjected to charge transfer impedance testing on an electrochemical workstation with a perturbation voltage of 10mV and a test frequency of 0.01-100000Hz. The charge transfer impedance of the battery was obtained by fitting the data using Zview.

[0125] Methods for testing the discharge capacity of batteries:

[0126] The assembled battery was subjected to charge and discharge tests in the Blue Battery Testing System. The charge and discharge current was 10mA / g, and the voltage range was 1.5-3.5V.

[0127] Test method for battery capacity retention after 200 cycles:

[0128] The assembled battery was subjected to an initial charge-discharge test on the Blue Electric test system at a current density of 10 mA / g within the 1.5-3.5V voltage range, and the discharge capacity was recorded as C1. The battery was then subjected to constant current charge-discharge at a current density of 50 mA / g within the 1.5-3.5V voltage range. After 200 cycles, the discharge capacity was recorded as C2, and the capacity retention rate after 200 cycles was C2 / C1.

[0129] Table 2

[0130]

[0131]

[0132] As can be seen from Table 1, compared with Comparative Examples 1-2, the contact angle between the separator and the electrolyte in Examples 1-27 was significantly reduced, and the charge transfer impedance was also significantly reduced. Furthermore, the ion transport number, discharge capacity, and capacity retention rate after 200 cycles were significantly improved in Examples 1-27. It is evident that by adding highly polar functional additives to the mixed slurry, Examples 1-27 can effectively improve the wettability of the composite separator in the electrolyte. At the same time, it can change the path of the positive electrode reaction and the morphology of the positive electrode products during discharge, promote the uniform and rapid passage of sodium ions through the composite separator and their transfer to the negative electrode, thereby optimizing the negative electrode-electrolyte-separator interface, thus improving the battery's discharge capacity and capacity retention rate after 200 cycles.

[0133] As can be seen from Table 1, compared with Comparative Example 2, the thermal shrinkage rate of the diaphragms in Comparative Example 1 and Examples 1-27 is significantly reduced, indicating that coating the surface of the PE diaphragm with inorganic ceramic materials can effectively improve the thermal stability of the diaphragm.

[0134] As can be seen from Table 1, compared with Examples 1-2 and Example 8, the charge transfer impedance of Examples 3-7 was further reduced, and the ion transport number, discharge capacity, and capacity retention rate after 200 cycles were further improved. It is evident that by limiting the mass ratio of inorganic ceramic material to 2,5-di-tert-butyl-1,4-benzoquinone to the range of (13-17):1, the wettability of the composite membrane in the electrolyte can be further enhanced, the path of the positive electrode reaction and the morphology of the positive electrode products during discharge can be changed, and sodium ions can be promoted to pass through the composite membrane uniformly and rapidly and be transferred to the negative electrode. This optimizes the negative electrode-electrolyte-membrane interface, thereby further reducing the charge transfer impedance of Examples 3-7 and further improving the ion transport number, discharge capacity, and capacity retention rate after 200 cycles.

[0135] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0136] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A composite diaphragm, characterized in that, include: Diaphragm substrate; A functional layer is disposed on at least one side of the membrane substrate. The functional layer includes inorganic ceramic materials, functional additives, binders, and dispersants. The functional additives include at least one of 2,5-di-tert-butyl-1,4-benzoquinone, 2-methylimidazolium, and 1,3-dimethyl-2-imidazolinone. The functional additives account for 4% to 16% of the mass of the functional layer.

2. The composite diaphragm according to claim 1, characterized in that, The mass ratio of the inorganic ceramic material to the functional additive is (5~19):1; Alternatively, the mass ratio of the inorganic ceramic material to the functional additive is (13~17):

1.

3. The composite diaphragm according to claim 1, characterized in that, The functional additive accounts for 5% to 10% of the mass of the functional layer.

4. The composite diaphragm according to claim 1, characterized in that, The inorganic ceramic material accounts for 75.5% to 94.3% of the mass of the functional layer, or 80% to 94.3% of the mass of the inorganic ceramic material in the functional layer. And / or, the adhesive accounts for 0.5% to 5.0% of the mass of the functional layer.

5. The composite diaphragm according to claim 1, characterized in that, The inorganic ceramic material includes at least one of alumina, boehmite, magnesium hydroxide, silicon dioxide, titanium dioxide, and zirconium oxide; And / or, the adhesive comprises at least one of polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylic acid, polyacrylonitrile and styrene-butadiene rubber; And / or, the membrane matrix includes at least one of polyethylene and polypropylene.

6. The composite diaphragm according to any one of claims 1 to 5, characterized in that, The functional layer also includes a wetting agent.

7. The composite diaphragm according to claim 6, characterized in that, The dispersant in the functional layer accounts for 0.1% to 1.0% by mass; And / or, the wetting agent accounts for 0.1% to 1.0% of the mass of the functional layer.

8. The composite diaphragm according to claim 6, characterized in that, The dispersant includes at least one of sodium carboxymethyl cellulose, polyvinylpyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; And / or, the wetting agent includes at least one of anionic surfactants, polyethylene surfactants, and polyol surfactants.

9. The composite diaphragm according to any one of claims 1 to 5, characterized in that, The composite diaphragm has a thermal shrinkage rate of less than 5% in the MD direction after baking at 150°C for 1 hour. And / or, the sodium ion transport number of the composite membrane immersed in the electrolyte is 0.2 to 0.

6.

10. A method for preparing the composite diaphragm according to any one of claims 1 to 9, characterized in that, include: Inorganic ceramic materials, functional additives, binders, dispersants, wetting agents, and solvents are mixed to form a slurry; The mixed slurry is coated on at least one side of the membrane substrate and dried to obtain a composite membrane.

11. The method according to claim 10, characterized in that, The solid content of the mixed slurry is 20wt% to 50wt%.

12. A battery, characterized in that, The composite membrane includes any one of claims 1 to 9, or the composite membrane prepared by the method described in claim 10 or 11.

13. An electrical appliance, characterized in that, It has the battery as described in claim 12.

Citation Information

Patent Citations

  • Composite diaphragm for sodium-ion battery as well as preparation method and application of composite diaphragm

    CN117638403A

  • Composite separator for lithium ion battery and preparation method therefor, and lithium ion battery

    WO2017063218A1